СУБКУЛЬТУРА НАРКОМАНІВ ЯК ОБ’ЄКТ КРИМІНОЛОГІЧНОГО АНАЛІЗУ - Гладкова, Євгенія Олексіївна (SUPREMANCE OF LAW, 2019)
The article deals with the drug addicts’ subculture as a specific kind of the criminal subculture. It examines the place of this subculture in the modern society, its influence on narcotization of society and spread of the drug-related crime, including its role in popularization of the fashion on drugs. Particular attention is paid to the connection between drug addicts’ subculture and, more broadly, drug-related subculture with the shadow market. Key features of the behavior of drug addicts and drug dealers within their respective subcultures are described.